Hello,

I have created the following simple function of the variable x,a, and b

f = 2*x – a – b.

What I want to do is set a and b equal to some constant values, for example a = b = 1. Now that I have set a and b equal to constants, my question is, how do I make this into a new function with just the variable x? For a = b = 1 , the new function should be 2*x – 2 . I want to do this so that I can use fzero to solve this new function numerically for x. Any help would be much appreciated.

## Best Answer